2020
DOI: 10.1108/jpif-12-2019-0151
|View full text |Cite
|
Sign up to set email alerts
|

Risks in feasibility and viability appraisal process for property development and the investment market in Nigeria

Abstract: PurposeThe feasibility and viability appraisal technique is becoming increasingly crucial in the planning systems, theory, applications and outputs for property development and project investments. This paper aims to account for the findings of the practices associated with risk in the feasibility and viability appraisal process. Also, it examines the need for a practical framework for conducting a feasibility and viability appraisal, which can be employed by estate surveyors and valuers in NigeriaDesign/metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A study that can be linked to this is that which revealed that about 75% of feasibility and Viability Appraisers in Nigeria though aware of the sensitivity analysis as a technique of investment appraisal don"t incorporate this veritable tool of risk analysis in investment appraisal. The tool which gives a good foothold in maximizing wealth, maximizing returns and minimizing risks has produced feasibility and viability report of commercial properties with less sophistication [18]; [19]. Flexibility in commercial properties can be achieved via certain ways.…”
Section: Resultsmentioning
confidence: 99%
“…A study that can be linked to this is that which revealed that about 75% of feasibility and Viability Appraisers in Nigeria though aware of the sensitivity analysis as a technique of investment appraisal don"t incorporate this veritable tool of risk analysis in investment appraisal. The tool which gives a good foothold in maximizing wealth, maximizing returns and minimizing risks has produced feasibility and viability report of commercial properties with less sophistication [18]; [19]. Flexibility in commercial properties can be achieved via certain ways.…”
Section: Resultsmentioning
confidence: 99%
“…Board's committees may also directly resist exploring new investment avenues if they fear the stock market will fail to properly value such investments [44]. Therefore, it is necessary to combine financial expertise with the investment attractiveness assessment process [45]. Since dealing with investment and financial sustainability issues requires long-term planning, the board of directors must have sufficient experience to encourage investors, which will lead to an increase in long-term financing [46].…”
Section: Moderator Rolesmentioning
confidence: 99%
“…These managers have significant financial expertise that may harm a firm and shareholders in the event of their withdrawal from the firm. Recently, directorship risk has emerged as a significant predictor that may significantly impact financial sustainability because of the directors' preferences and choices throughout their directorship portfolio [45]. In addition, managers who leave their riskiest management positions are more experienced and have more education than others in the field.…”
Section: Moderator Rolesmentioning
confidence: 99%
“…The property development process starts from feasibility, project concept with output feasibility analysis, project management, marketing and disposal [10]. These processes are usually interrelated in the completion of property development and have their respective complexities at each stage [11]. One of the complexities in a property development project comes from stakeholders who have different needs, interests and concerns that can negatively or positively affect the project [12].…”
Section: Performance-based Design In Property Developmentmentioning
confidence: 99%